ALTERNATIF STRATEGI PEMBELAJARAN PAI DI TENGAH WABAH COVID-19: (Studi Tentang Inovasi dan Kreativitas Pendidik di MTS. N 02 Simeulue) - Iqbal, M.; Siahaan, Abdurrahman; Mustafa, Ahmad; Ramadhan, Bertha Zulmiadi (Jurnal Bilqolam Pendidikan Islam, 2020)
In a pandemic like today, alternative strategies in learning are needed by utilizing technology which for now can be said to be advanced and sophisticated, but we cannot rule out the possibility of learning that is carried out online which causes pros and cons both from teachers, students and parents of students, especially those who have a poor economy, innovation and creativity of teachers as educators are needed, at least with the innovation in learning strategies during Covid-19 this can make it easier for students to understand and get education even though they cannot learn face-to-face with teachers or educators. So the teachers, especially the PAI teachers at Mts. N simuelue Aceh, has tried to make several innovations in learning strategies during the Covid-19 period. If before the Covid-19 pandemic the learning strategy carried out at Mts. N 02 simuelue, is a deductive and inductive strategy. A deductive learning strategy is a strategy that is carried out by studying the concepts first, then looking for conclusions and illustrations from the material learned from abstract things then going to concrete things and commonly called general to specific learning strategies. In contrast, the inductive learning strategy is learning done from understanding concrete things and then being exposed to complex and difficult material and is commonly called a special to general learning strategy. However, after the Covid-19 pandemic the teachers pursued innovation and adopted alternative strategies, namely by applying the cooperative e-learning method, carrying out learning by prioritizing student activity and cooperation with one another to keep students enthusiastic and to maintain solidarity and feeling. mutual respect even when learning is done online. This study aims to make us understand the extent of innovation of the Pai teachers at Mts. N 02 Simuelue on creativity in learning amid the covid-19 outbreak.